A revisit of the environmental Kuznets curve hypothesis for Turkey: new evidence from bootstrap rolling window causality - Ozcan, Burcu; Apergis, Nicholas; Shahbaz, Muhammad (Springer Heidelberg, 2018)
This study aims at analyzing the Environmental Kuznets Curve (EKC) hypothesis for Turkey, spanning the period of 1961-2013. Unlike previous studies, instead of carbon emissions, the ecological footprint is used as a proxy for environmental degradation. Moreover, a bootstrap time-varying causality approach is used to detect the possible changes in causal relations and to obtain the parameters across subsample periods. The results clearly indicate that there are feedback relationships between economic growth and the ecological footprint in some subsample periods. In addition, the impact of economic growth on environmental degradation is positive and has a slowly increasing trend in all subsample periods. Therefore, the EKC hypothesis is not confirmed for the Turkish economy. Based on these results, some crucial policy implications are suggested.
Keywords: Environmental Kuznets curve; Economic growth; Ecological footprint; Time-varying causality; Turkey